The role of digital technologies in education - Senkivska, L. (Journal of Education, Health and Sport, 2022)
The article analyzes the role of digital technologies in the educational process. It is determined that digital technologies allow to focus the educational process not only on meeting the requirements of professional and educational standards, but on the formation of professional culture of the future specialist, the desire for continuous self-improvement through information services and technologies.